2017
DOI: 10.15343/0104-7809.20174104588596
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento sedentário e massa muscular reduzida em idosos: um estudo de base populacional

Abstract: ResumoThe loss of muscle mass in older adults is negatively associated with health, which makes it necessary to identify modifiable behavioral habits that may aggravate this condition in this population. In this context, the objectives of the present study were to describe the characteristics of older adults according to reduced muscle mass status and verify its association with sedentary behavior. This was a cross-sectional population-based study, conducted in 24 cities in the Regional Healthcare Administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
1
1
0
2
Order By: Relevance
“…The present study identified a high prevalence of low muscle reserve, as more than 1/5 of the older people had this condition. This finding corroborates the results of Martins Resende et al (2017) 18 who, when observing older people in Uberaba, found a prevalence of LMR of 20.9%, measured by LC, using the cutoff point proposed by the World Health Organization (1995)9 (< 31 cm of LC for reduced muscle mass). On the other hand, it was lower than that found by Machado et al (2019) 19 , who observed a prevalence of 28.4% of low muscle reserve in community-dwelling older women in São Paulo, based on dual-energy X-ray absorptiometry (DXA).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present study identified a high prevalence of low muscle reserve, as more than 1/5 of the older people had this condition. This finding corroborates the results of Martins Resende et al (2017) 18 who, when observing older people in Uberaba, found a prevalence of LMR of 20.9%, measured by LC, using the cutoff point proposed by the World Health Organization (1995)9 (< 31 cm of LC for reduced muscle mass). On the other hand, it was lower than that found by Machado et al (2019) 19 , who observed a prevalence of 28.4% of low muscle reserve in community-dwelling older women in São Paulo, based on dual-energy X-ray absorptiometry (DXA).…”
Section: Discussionsupporting
confidence: 91%
“…Associated with this quantification, it advocates the assessment of muscle strength, in which a dynamometer is used, an instrument that measures handgrip strength 6 . In this sense, recent studies highlight LC as a more accessible marker, when compared to the others, important for screening individuals affected by the disease 10,18,21 and widely used for the indirect assessment of muscle mass in population studies 21,22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…O excesso de peso esteve negativamente associado ao desfecho (Tabela 3). 18 que ao observar idosos de Uberaba, encontraram prevalência de BRM de 20,9%, aferida pelo PP, utilizando o ponto de corte proposto pela Organização Mundial da Saúde (1995) 9 (< 31 cm de PP para massa muscular reduzida). Por outro lado, foi inferior ao encontrado por Machado et al (2019) 19 , os quais observaram uma prevalência de 28,4% de baixa reserva muscular em idosas da comunidade em São Paulo, a partir de absorciometria de raios X de dupla energia (DXA).…”
Section: Resultsunclassified
“…Associados à essa quantificação, preconiza a avaliação da força muscular, na qual se utiliza o dinamômetro, instrumento que mede a força de preensão palmar 6 . Neste sentido, estudos recentes destacam o PP como um marcador mais acessível, quando comparado aos demais, importante para a triagem de indivíduos acometidos pela doença 10,18,21 e muito utilizado para a avaliação indireta da massa muscular em estudos populacionais 21,22,23 .…”
Section: Resultsunclassified